FORMULATION AND CARACTERIZATION OF QUERCETIN NIOSOME WITH CONCENTRATION VARIATIONS OF SPAN 20 SURFACTANT - Weka Sidha Bhagawan; Rahmi Annisa; Atiza Fajrin Maulidya (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2021)
Quercetin has low solubility, absorption and bioavailability which limits its practical use as a drug or supplement. Therefore, it is important to formulate a quercetin niosome system with various concentrations of span 20 as a surfactant. This investigation aimed to formulate and analyse a quercetin niosome preparation with span 20 variations to provide optimal quercetin solubility. Niosomes were prepared using various concentrations of span 20. In the present study, the quercetin niosome used the reverse phase evaporation (RPE) method. Quercetin niosome is characterised by its organoleptic properties, pH value, particle morphology comprising the particle shape and size, and encapsulation efficiency. Organoleptic observations of the quercetin niosome included a yellow colour, distinctive quercetin odour and thick consistency for all formulas. The pH remained within the physiological pH range of skin. Quercetin niosome morphology was close to spherical while the niosome particle size results were 2.13 µm (F1), 2.99 µm (F2) and 3.31 µm (F3). The quercetin niosome encapsulation efficiency results were 81.86 ± 0.47% (F1), 84.02 ± 0.26% (F2) and 88.24 ± 0.10% (F3). Quercetin niosome were successfully prepared using multiple span 20 concentrations below the cholesterol concentration characterised by the measurement results of organoleptic, pH, particle morphology and encapsulation efficiency.